Human transgression - divine retribution : a study of religious transgressions and punishments in Greek cultic regulation and Lydian-Phrygian propitiatory inscriptions ('confession inscriptions') - Rostad, Aslak, (Archaeopress Archaeology, 2020)
This text analyses pagan concepts of religious transgressions as expressed in Greek cultic regulations from the 5th century BC-3rd century AD. Also considered are so-called propitiatory inscriptions from the 1st-3rd century AD Lydia and Phrygia, in light of 'cultic morality', intended to make places, occasions, and worshippers suitable for ritual.